2016
DOI: 10.1161/hypertensionaha.115.06849
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Hypertension-Associated Protein Aggregates in Mouse Heart Have Similar Proteomic Profiles

Abstract: Neurodegenerative diseases are largely defined by protein aggregates in affected tissues. Aggregates contain some shared components as well as proteins thought to be specific for each disease. Aggregation has not previously been reported in the normal, aging heart or the hypertensive heart. Detergent-insoluble protein aggregates were isolated from mouse heart and characterized on 2D gels. Their levels increased markedly and significantly with aging and following sustained angiotensin-II-induced hypertension. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 56 publications
(56 reference statements)
2
67
0
Order By: Relevance
“…Total aggregates increase with age in normal C. elegans (David et al ., 2010; Ayyadevara et al ., 2014) and in several tissues of normal mice (Ayyadevara et al ., 2016 and unpublished data), indicating that protein aggregation is a quite broadly conserved feature of aging. In view of our evidence for common processes underlying the growth of both Aβ and tau aggregates, as discussed above, it is surprising that ‘total aggregates’ (sarcosyl‐insoluble material without IP) differed far less between AD and NC than did either type of neuropathological aggregate.…”
Section: Discussionmentioning
confidence: 77%
“…Total aggregates increase with age in normal C. elegans (David et al ., 2010; Ayyadevara et al ., 2014) and in several tissues of normal mice (Ayyadevara et al ., 2016 and unpublished data), indicating that protein aggregation is a quite broadly conserved feature of aging. In view of our evidence for common processes underlying the growth of both Aβ and tau aggregates, as discussed above, it is surprising that ‘total aggregates’ (sarcosyl‐insoluble material without IP) differed far less between AD and NC than did either type of neuropathological aggregate.…”
Section: Discussionmentioning
confidence: 77%
“…As shown in Supplemental Figure 3C, the levels of overexpressed HSPB8 were significantly BAG3 deficiency leads to increased levels of a subset of insoluble proteins. Recent studies have found that, despite a paucity of age-dependent differences in the total cardiac proteome, significant age-dependent differences are observed among proteins isolated from detergent-insoluble protein aggregates (48,49). Therefore, since we observed no significant changes in the total proteome of cardiac tissue from BAG3-deficient mice (Supplemental Figure 6), we next analyzed insoluble proteins by isolating detergent-insoluble protein fractions from BAG3-CKO and control hearts.…”
Section: Resultsmentioning
confidence: 93%
“…Mouse models that are genetically engineered to express exclusively aggregate prone proteins in cardiomyocytes have progres sive cardiac remodelling 148 . Moreover, emerging evidence suggests that accumulating cardiac protein aggregates are early events in both ageing and angiotensin II induced hypertension in mice 149 . These experimental data prov ide evidence that sole derailment of proteostasis in cardiomyo cytes suffices to initiate cardiac remodelling, ultimately resulting in cardiac failure.…”
Section: Nature Reviews | Cardiologymentioning
confidence: 99%